Applications of pentamethyl phenyl ketones in the synthesis of carbocycles and heterocycles - Lunt-Laurin, CE (2023)
Chapter 1: Introduction. The introduction covers an overview of hydrogen borrowing and the types of hydrogen borrowing strategies. The challenges and advantages of hydrogen borrowing strategies. The structure of Ph* ketones and how this can be utilised in synthesis.